Arachidonate-Induced Fibrinogen Binding To Thrombin-Degranulated Rabbit Platelets Is Independent Of Released ADP - Harfenist, E J; Guccione, M A; Packham, M A; Kinlough-Rathbone, R L; Mustar, J F (Thrombosis and Haemostasis, 1981)
When human or rabbit platelets are stimulated with ADP, fibrinogen (Fbg) binding sites are revealed, the platelets bind Fbg and aggregate. Since stimulation with other aggregating agents (arachidonate, collagen or ionophores) releases platelet granule contents, including ADP and Fbg, it is difficult to determine whether these agents cause aggregation or Fbg binding that is independent of ADP. Therefore we treated rabbit platelets with thrombin (0.73 U/ml) to release at least 90% of their dense granule contents, as measured by 14C-serotonin, washed and resuspended them, and studied aggregation and Fbg binding upon stimulation with ADP or arachidonate. In the presence of Fbg, thrombin-degranulated platelets (TDP) aggregate in response to ADP or arachidonate at concentrations that aggregate untreated platelets, although TDP aggregate somewhat less extensively. When TDP are aggregated with 50 μM arachidonate, they lose up to 9% of their remaining serotonin, corresponding to a concentration of ADP in the suspending medium of not more than0.06μM, which does not aggregate TDP or cause detectable Fbg binding. When creatine phosphate/creatine phosphokinase (CP/CPK) is added at a concentration that abolishes aggregation in response to 1 μM ADP, it reduces aggregation caused by arachidonate by only 18%. Binding studies with 125I-Fbg show that stimulation of TDP with either ADP or arachidonate results in specific Fbg-binding similar to the binding to ADP-stimulated normal platelets. CP/CPK almost completely inhibits binding induced by ADP but reduces binding induced by arachidonate by only 30%. Aggregation and binding studies with TDP using a combination of arachidonate with low concentrations of ADP failed to show synergistic effects. Thus arachidonate causes aggregation and Fbg binding to TDP that are independent of ADP, although the magnitude of these effects may be increased by released ADP.